Optimal grasp planning for a dexterous robotic hand using the volume of a generalized force ellipsoid during accepted flattening. (11th January 2017) - Jia, Peng; Li, Wei li; Wang, Gang; Li, Song Yu
A grasp planning method based on the volume and flattening of a generalized force ellipsoid is proposed to improve the grasping ability of a dexterous robotic hand. First, according to the general solution of joint torques for a dexterous robotic hand, a grasping indicator for the dexterous hand—the maximum volume of a generalized external force ellipsoid and the minimum volume of a generalized contact internal force ellipsoid during accepted flattening—is proposed. Second, an optimal grasp planning method based on a task is established using the grasping indicator as an objective function. Finally, a simulation analysis and grasping experiment are performed. Results show that when the grasping experiment is conducted with the grasping configuration and positions of contact points optimized using the proposed grasping indicator, the root-mean-square values of the joint torques and contact internal forces of the dexterous hand are at a minimum. The effectiveness of the proposed grasping planning method is thus demonstrated.